User interface and user experience design for the TB.berkat rezeki website - Stephen Aprius Sutresno; Henoch Juli Christanto; Yerik Afrianto Singgalen; Elfin Saputra; Biafra Daffa Farabi; Bernardus Alvin Rig; Radyan Rahmananta; Octa Hutapea (Institute of Computer Science (IOCS), 2024)
In the era of continuous technological advancement, the presence of a website becomes crucial, especially for businesses aiming to harness digital potential. This research aims to address the issue of the lack of digital presence and e-commerce sites for TB. Berkat Rezeki, a building equipment store in Bekasi, West Java. By adopting the Design Thinking method, this study focuses on the development of a website with a UI/UX layout that supports an intuitive and satisfying online shopping experience. Survey results indicate that 64% of the Indonesian population are internet users, signaling a vast digital market potential. Applying the principles of Design Thinking, particularly in the Empathize, Define, Ideate, Prototype, and Testing stages, this e-commerce system is designed to create a clear layout, attractive design, and a responsive user experience. Evaluation using the System Usability Scale (SUS) shows an average score of 72, categorized as